PENDEKATAN SISTEM PEMBELAJARAN IPS DI MTSS AL- WASHLIYAH PEMATANG JOHAR - Dalimunthe, Torkis Dalimunthe; Muhammad Alif Muchlisin; Feny Rosanti; Defriani (Cv Arsy Persada Quality, 2022)
This study aims to analyze the role of the principal in improving the performance of SD Muhammadiyah Karangturi Yogyakarta teachers, as well as the supporting and inhibiting factors in improving the performance of SD Muhammadiyah Karangturi Yogyakarta teachers. This research uses qualitative research with narrative-analytic method. To receive data, researchers go directly to the field (field research). In analyzing the data, the researcher gradually used data reduction, data presentation, and data verification. Also analyze the performance of teacher researchers using data indexing techniques. The results of this survey indicate that the principal in carrying out his duties as the chief executive of this forum has a positive effect on improving the performance of the teachers of SD Muhammadiyah Karangturi. It is clear that (a) teachers are ready to implement the new curriculum. (b) Teachers use more creative and innovative teaching strategies. (c) Teachers can assess student learning outcomes against relevant curriculum requirements, namely cognitive, affective and psychomotor aspects. (d) Teachers not only teach material but also moral responsibility.